2011
DOI: 10.1111/j.1540-627x.2011.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human and Social Capital on Entrepreneurs’ Knowledge of Finance Alternatives

Abstract: Building upon prior research that demonstrates how the limited knowledge of finance alternatives of entrepreneurs may cause suboptimal finance decisions, this paper examines how entrepreneurs' human and social capital influence their knowledge of finance alternatives. For this purpose, we use survey data from 103 Belgian start-ups. Results demonstrate that entrepreneurs with a business education and entrepreneurs with experience in accountancy or finance have a broader knowledge of finance alternatives. Having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
107
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 57 publications
11
107
0
2
Order By: Relevance
“…In summary, crowdfunding literature consistently argues for the importance of social networks as well as the effective management of these networks (Mollick 2012;Hui et al, 2013), which is also echoed by findings in the entrepreneurial literature (Molina-Morales and -Fernadez, 2010;Seghers et al, 2012;Durkin and McGowan 2013;Sigmund et al, 2013). For SMEs however this can prove difficult due to their resource poverty, which can mean their execution of, and ability to manage social networks is haphazard and informal (Gilmore et al, 2001;Franco et al, 2014), and lacks purposeful use (Durkin and McGowan, 2013).…”
Section: Crowdfunding and Network Managementmentioning
confidence: 90%
“…In summary, crowdfunding literature consistently argues for the importance of social networks as well as the effective management of these networks (Mollick 2012;Hui et al, 2013), which is also echoed by findings in the entrepreneurial literature (Molina-Morales and -Fernadez, 2010;Seghers et al, 2012;Durkin and McGowan 2013;Sigmund et al, 2013). For SMEs however this can prove difficult due to their resource poverty, which can mean their execution of, and ability to manage social networks is haphazard and informal (Gilmore et al, 2001;Franco et al, 2014), and lacks purposeful use (Durkin and McGowan, 2013).…”
Section: Crowdfunding and Network Managementmentioning
confidence: 90%
“…Indeed, stimulating the demand for external finance is an important objective to increase entrepreneurial ambition in firms. Research shows that entrepreneurs with higher levels of human capital and more extensive networks have a greater knowledge of financial options (Seghers et al 2012). …”
Section: Types Of Finance Needed To Fund High Growthmentioning
confidence: 99%
“…The entrepreneurship literature has found that nascent entrepreneurs with prior entrepreneurial or managerial experience have knowledge regarding the various activities associated with starting a firm, including how to develop contacts with customers and financiers, gather and allocate resources, organize internal processes and structures, attract and retain employees (Delmar, Shane 2006;Dimov 2010;Grichnik et al 2014). Given the importance of the domain specific insights, young inexperienced entrepreneurs lack important knowledge about the ways to address liabilities and constraints when starting a new business and competing for resources (Grichnik et al 2014;Hitt et al 2001;Seghers et al 2012). Prior entrepreneurial and managerial experiences provide greater repertoire of skills needed to start a new business (Kim et al 2006).…”
Section: Resources and Industry Choicementioning
confidence: 99%
“…Inexperienced young entrepreneurs usually have troubles trying to assess resources they need and barriers they may face (Hitt et al 2001;Seghers et al 2012;Grichnik et al 2014). As universities provide a set of various valuable insights, education may partly serve as a substitute of experience (Shane 2000;Zhao et al 2005).…”
Section: Resources and Industry Choicementioning
confidence: 99%